A cracking oxygen story: A new view of stress corrosion cracking in titanium alloys. (1st April 2022) - Joseph, Sudha; Kontis, Paraskevas; Chang, Yanhong; Shi, Yitong; Raabe, Dierk; Gault, Baptiste; Dye, David
Abstract: Titanium alloys can suffer from halide-associated stress corrosion cracking at elevated temperatures e.g., in jet engines, where chlorides and Ti-oxide promote the cracking of water vapour in the gas stream, depositing embrittling species at the crack tip. Here we report, using isotopically-labelled experiments, that crack tips in an industrial Ti-6Al-2Sn-4Zr-6Mo alloy are strongly enriched (>5 at.%) in oxygen from the water vapour, far greater than the amounts (0.25 at.%) required to embrittle the material. Surprisingly, relatively little hydrogen (deuterium) is measured, despite careful preparation and analysis. Therefore, we suggest that a combined effect of O and H leads to cracking, with O playing a vital role, since it is well-known to cause embrittlement of the alloy. In contrast it appears that in α + β Ti alloys, it may be that H may drain away into the bulk owing to its high solubility in β -Ti, rather than being retained in the stress field of the crack tip. Therefore, whilst hydrides may form on the fracture surface, hydrogen ingress might not be the only plausible mechanism of embrittlement of the underlying matrix. This possibility challenges decades of understanding of stress-corrosion cracking as being related solely to the hydrogen enhanced localised plasticity (HELP) mechanism, which explains why H-doped Ti alloys are embrittled. This would change the perspective on stress corrosion embrittlement away from a focus purely on hydrogen to also consider the ingress of O originating from the water vapour, insights critical for designing corrosion resistant materials. Graphical abstract: Image, graphical abstract